The Construction of Interactive Teaching Quality Monitoring System From the Perspective of Psychology - Chen, Kewei (Frontiers in Psychology, 2022)
The article first proposes a reflection on the status quo of classroom teaching in public universities, selects a large number of educational scenes, and analyzes these selected educational concepts in detail from a theoretical perspective. Through the establishment of a teaching quality monitoring system based on careful observation and analysis, several major problems in public university classrooms have been discovered: poor classroom interaction mode, single classroom interaction mode, low classroom interaction efficiency, and inefficient classroom interaction feedback. Summarizing the causes of classroom interaction problems, the article summarizes three factors: teachers, students, and the macro environment. In the experiment, 85% of the students thought that the teacher-student relationship was relatively ordinary. Among the 11 students who participated in the experiment, 60% of the students were very active in interactive classroom discussions. Therefore, based on the analysis of problems and factors, the article puts forward an optimization strategy to create a classroom interaction atmosphere, improve classroom interaction mode, improve classroom interaction efficiency, and strengthen classroom interaction feedback. In particular, it promotes the integration of teacher-student relationship, emphasizes the role of students, improves the level of classroom interaction, creates conditions for classroom interaction, improves teacher-student interaction control ability, enhances student interactive speech ability, strengthens error correction and feedback, and increases multiple feedback methods.